Autism spectrum disorder: an audiological perspective - Dzulkarnain, Ahmad Aidil Arafat (2020)
This talk will discuss the difficulties faced by autism disorder (ASD) patients. Typically, standard audiology assessments will reveal they have no hearing impairment. At the same time, ASD patients are often associated with sensory processing disorder including abnormal hearing sensitivities. This talk will describe some electrophysiological findings that could explain their abnormal hearing sensitivities and how this is related to the auditory system.